FORMULATION AND CHARACTERIZATION OF ISRADIPINE SOLID DISPERSION WITH ENHANCED SOLUBILITY - FAKHRULDEEN, ZAID HADI; ABDUL-HASAN, MAZIN THAMIR (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to prepare and optimize solid dispersion of isradipine, an antihypertensive drug with poor aqueous solubility using two different methods, namely, solvent evaporation and fusion. Methods: Twenty-two formulas of isradipine solid dispersion were prepared using one of the following carriers: Poloxamer 407 (PXM 407), Polyethylene Glycol 4000 (PEG 4000), Polyethylene Glycol 6000 (PEG 6000) and urea at different carrier-to-drug ratios. The produced solid dispersion formulations were evaluated for their percentage yield, drug content, solubility, and in vitro dissolution. Further investigations were performed for the selected formula; these include Differential Scanning Calorimetry (DSC), and Powder X-Ray Diffraction (PXRD) studies to evaluate the crystalline state of the drug. Besides Fourier Transformation Infrared (FTIR) spectroscopy was conducted to evaluate drug-carrier compatibility. Results: The results of this study showed that all the prepared formulas resulted in improvement in saturation solubility. Run 14 (which consists of PXM 407: isradipine in a 5:1 ratio) demonstrated a substantial increase in solubility, resulting in approximately 16 times higher solubility than the pure drug. The results of DSC and PXRD studies demonstrated complete dispersion of the drug in the carrier or amorphization of the drug. Furthermore, FTIR results indicated drug-carrier compatibility. Conclusion: From this study, it was evident that solid dispersion of isradipine in the previously mentioned carriers is an effective and efficient method to enhance its solubility. The best solubility enhancement and release profile was observed in run 14 (which combines PXM 407: isradipine in a 5:1 ratio), which was selected as the optimum formula.